Exchange rate pass-through, monetary policy and real shocks: an empirical evaluation - Aguirre, Horacio A. (2018)
We look at a panel of Latin American countries from 1970 and 2016 to enquire how exchange rate pass-through has changed over time, and whether this owes to monetary or real shocks hitting the economy. We estimate conventional pass-through measures, both short and long run; then we obtain rolling estimates of those measures, and relate them to monetary and real variables using fixed effect models. We find that: in keeping with previous studies, pass-through coefficients have fallen sharply in recent decades in Latin America; money growth tends to be strongly associated to short-run exchange rate pass through, with a small influence of real shocks such as terms-of-trade changes; money growth is also associated to long-run pass-through, while terms of trade shocks are more statistically significant. Results are consistent with the hypothesis that ERPT changes with the kind of shock and the monetary policy response to it.